Vibration and voice operated navigation system for visually impaired person - Mahmud, Nasif; Saha, R. K.; Zafar, R. B.; Bhuian, Dr. Md. Belal Hossain; Sarwar, Shahzad S. (IEEE Computer Society, 2016)
This conference paper was presented in the 2014 International Conference on Informatics, Electronics and Vision, ICIEV 2014; Dhaka; Bangladesh; 23 May 2014 through 24 May 2014 [© 2014 IEEE Computer Society] The conference paper's definite version is available at: http://10.1109/ICIEV.2014.6850740